ANALISIS BAURAN PEMASARAN VILLA GUNUNG LESTARI CIPUTAT - TANGERANG SELATAN BERDASARKAN PREFERENSI KONSUMEN - , Ali Subhan; , Prof. Bambang Riyanto L.S., M.B.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Increasing in housing needs is resulting in intense of competition among the property developers and motivates them to competing offers the best for the consumers. Prediction about the consumer preferences for marketing mix are attached to the housing becomes an important aspect in marketing. Products, prices, and places of the marketing mix which have the best values will help developers get the benefits from the competition. Thatâs why this research is conducted with the aim to analyze the marketing mixes which became the main preferences of consumers in buying a house. The marketing mixes used in this research are kind of product, quality, house designs, house features, weigh of house, services, list of price, discount, special price, type of credit and location. The data used in this research consist of the primer data and supported by secondary data. Primer data are obtained from the questionnaire result of the consumers who buy the house in the Villa Gunung Lestari. The analysis tool used is exploratory factor analysis and Mann-Whitney U test. This factor analysis is used to generate the factors which are become consumersâ preference in selecting Villa Gunung Lestari as their decision, and Mann-Whitney U analysis is used to result the different of preferences between the high income and low income of the consumers using the SPSS software. With this factor analysis, researcher found that there are two factors became consumers preference. The first factors consist of kind of product, discount, special price, type of credit, and place while the second factor consist of the variable of quality, design, house feature, house weigh, services, and list of price. Using Mann-Whitney U analysis, researcher found that from two factor conducted there are significant different preference between the high income and low income customers. Key word: variable, factor analysis, Mann-Whitney U analysis, housing, preferences